Pump-Probe Ghost Imaging with SASE FELs - D. Ratner (Physical Review X, 2019)
In this paper, we propose a new approach to measuring ultrafast dynamics with free-electron lasers (FELs). Ultrafast experiments are among the most promising avenues of research at x-ray FELs, with the potential to reveal the chemical dynamics of charge separation, conical intersection crossing, and biologically mediated reactions. Pump-probe scanning is the standard approach to measure dynamics at x-ray FELs, but at the shortest timescales, and particularly for x-ray pump, x-ray probe experiments, the scans require challenging beam setups and can introduce systematic errors. Here, we propose an alternative approach using the randomness of the self-amplified spontaneous emission (SASE) process to drive many simultaneous pump-probe experiments on each shot. Measuring the fluctuations in the incident beam’s time profile on a shot-to-shot basis enables the reconstruction of ultrafast dynamics down to the coherence length of the FEL without the need for pump-probe scans. Because of similarity to ghost imaging, in which spatial properties are reconstructed by measuring the incident probe’s transverse properties, we call this “pump-probe ghost imaging.” In this paper, we describe the method and simulate an example experiment. We also describe an alternative implementation that uses only spectral measurements, avoiding the need for direct time-domain diagnostics and extending the method to the attosecond regime.